Synthesis of Geopolymer from Ferronickel Aluminosilicate Waste - Samadhi, Tjokorde Walmiki; Wulandari, Winny; Dwinidasari, Aya Anisa; Rahmasari, Arum (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The nickel industry in Indonesia generates massive volumes of ferronickel slag that may harm the environment. This research evaluates the feasibility of utilizing coal fly ash and slag from a ferronickel smelter in Obi Island in Indonesia to synthesize geopolymer, an environmentally friendly cementitious material. Compressive strength of geopolymer mortars was measured as a function of slag particle size (coarse and fine), fly ash mass fraction in the dry aluminosilicate binder precursor blends (0.4 and 0.8), and thermal curing period (24 and 48 hours). Mortar specimens were produced by mixing ash and slag with activator solution and sand. The activator solution contained Na2SiO3 and NaOH at a mass ratio of 2:1. Solid reactants to activator solution mass ratio was 3.33. After heat curing, specimens were held in ambient conditions to an age of 7 days. The compressive strength of the mortars was in the 2.1-24.8 MPa range. Geopolymer mortars were able to comply to Indonesian SNI 15-2049-2004 or US ASTM C1329-05 standards for Portland cement. FTIR and XRD characterizations confirmed the conversion of fly ash and slag into amorphous geopolymers at near ambient temperature. Finer slag particle size increased reactivity, ultimately producing higher compressive strength.